Writinscreening, speech position, and autoethnography: the importance of anti-racist researches (PerCursos, 2024)
One aspect of the coloniality of knowledge is the subalternation of knowledge and wisdom, constructing a hierarchy of knowledge. In attempting to problematize and socialize specific topics in their terms and concepts, we may sometimes generalize and/or universalize them, overlooking their singularities and origins, thus depriving historically subalternized groups of the right to speak and enunciate. It occurs when our openness to diversity and difference is grounded in multicultural differentials and/or assimilationist perspectives. This essay aims to understand how, in our quest to become anti-racist researchers, we can empty particular meanings and sensations from terms and/or concepts by removing them from their original contexts, thereby universalizing the specific and reinforcing epistemic racism. We employ a qualitative method with an emphasis on literature review to identify potential misconceptions in the understanding and use of concepts such as "Escrevivência" (Evaristo, 2020) and "Lugar de Fala" (Ribeiro, 2019). The challenge in using these concepts leads us to research the autoethnographic method. Situated among participatory research methods, autoethnography enables the researcher to approach the subject/territory of research, helping them deal with their impulses, feelings, and emotions regarding the object/subject of research and their culture. An investigation from an autoethnographic perspective serves as a position of speech for researchers who, aware of the demands of navigating cultural borderlands, draw on the contributions of thinkers immersed in the themes and contexts under study. This method involves cultural and autobiographical guidance in interpreting the accessed content, allowing researchers to continue their journey in racial literacy.
Keywords: writinscreening; speech position; autoethnography